Numerical Study on the Seismic Retrofitting of Masonry-Infilled RC Frames Using Textile-Reinforced Mortar - Filippou, Christiana (Department of Civil Engineering and Geomatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2021)
Most of the existing reinforced concrete buildings with masonry infill walls around the world have been built before the development of new seismic regulations posing them more susceptible to collapse during an earthquake event. For this reason, the seismic retrofitting of existing infilled frame buildings is nowadays one major challenge of earthquake risk mitigation. Over the past decade, the Textile Reinforced Mortar (TRM) composite material, encompassing a combination of inorganic matrix (lime- or cement-based) and non-corrosive multi-axial textile fabrics, has emerged as a promising novel alternative for seismic retrofitting of masonry-infilled RC frame buildings. Nevertheless, a deeper investigation in the research area of TRM is required considering the lack of design guidelines, the limited existing research regarding the use of TRM for retrofitting masonry-infilled RC frames, and the need to enhance the implementation of this composite material as a regular method for retrofitting existing buildings in practical engineering. In this context, the present study focuses on investigating numerically the seismic retrofitting of masonry-infilled RC frames using TRM. Essential step towards this direction is the development of a simplified model able to predict the tensile behavior of TRM. The study conducted herein has three main contributing parts. In the first part, a new simple and easy to-implement analytical model able predict the tensile behavior of TRM in terms of stress-strain is proposed. The proposed model, which extends an established model that applies for fiber-brittle matrix to TRM, using recommendations for reinforced concrete, proved accurate, since the analytical curves properly fit with those obtained from relevant available experimental studies. A parametric study is also performed to examine the sensitivity of the proposed model to a range of parameters. In the second part of this study, a detailed finite element model of the masonry-infilled RC frame, with and without TRM, considering the infill-frame interaction and the non-linear behavior of the constituent components of the structure, and using the proposed analytical model of TRM to define the tensile behavior of TRM, has been developed and validated using selected experimental study conducted in the past. Sensitivity analyses are then performed to examine the behavior of integral and non-integral infilled frames subjected to in-plane cyclic loading, and to investigate the influence of the stiffness properties of the infill-frame interface on the in-plane cyclic response of retrofitted infilled frame model. The third part of the study focuses on investigating numerically the parameters that affect the in-plane behavior of masonry infilled-RC frames retrofitted with TRM under cyclic loading such as: the TRM reinforcement ratio and the type of mortar used for binding the textile reinforcement. Furthermore, the effect of the presence of different size of central opening on the lateral response of masonry-infilled RC frames subjected to cyclic loading is studied, and the use of TRM for retrofitting masonry-infilled RC frames with openings is also investigated by carrying out numerical experiments. As part of this study, a detailed review of the broader literature in the area of infilled frames and in the area of TRM as a composite material, and as a method for retrofitting masonry-infilled RC frames was undertaken. As a result of this research work, it was concluded that the TRM can be considered as a suitable method for seismic retrofitting masonry-infilled RC frame buildings with and without openings. Moreover, the proposed analytical model of TRM can be useful to facilitate the implementation of numerical models of retrofitted structures using TRM, and further to develop design guidelines. The research work, presented in this thesis, is valuable as it contributes to expand the knowledge related to TRM, while promoting the prospective use of this novel material for retrofitting existing structures.
Keywords: Textile Reinforced Mortar (TRM); Masonry-infilled RC frames; Openings; Cyclic loading; Non-linear analysis; Finite element modeling; Analytical modeling